(untitled) (Texas Journal of Medical Science, 2024)
The article examines the role of nitric oxide in the regulation of peripheral vascular tone in children with neurocirculatory dystonia. When using a functional test with reactive hyperemia, its high diagnostic significance was revealed; a decrease in the formation of nitric oxide in the vascular endothelium (endothelial dysfunction) was established in children with neurocirculatory dystonia (p <0.001).